When musical accompaniment allows the preferred spatio-temporal pattern of movement - Emmanouil, A.; Rousanoglou, E.; Georgaki, G.; Boudolos, K. D. (Sports Medicine International Open, 2021)
A musical accompaniment is often used in movement coordination and stability exercise modalities, although considered obstructive for their fundament of preferred movement pace. This study examined if the rhythmic strength of musical excerpts used in movement coordination and exercise modalities allows the preferred spatio-temporal pattern of movement. Voluntary and spontaneous body sway (70 s) were tested (N=20 young women) in a non-musical (preferred) and two rhythmic strength (RS) musical conditions (Higher:HrRS, Lower:LrRS). The center of pressure trajectory was used for the body sway spatio-temporal characteristics (Kistler forceplate, 100 Hz). Statistics included paired t-tests between each musical condition and the non-musical one, as well as between musical conditions (p=0.05). Results indicated no significant difference between the musical and the non-musical conditions (p>0.05). The HrRS differed significantly from LrRS only in the voluntary body sway, with increased sway duration (p=0.03), center of pressure path (p=0.04) and velocity (p=0.01). The findings provide evidence-based support for the rhythmic strength recommendations in movement coordination and stability exercise modalities. The HrRS to LrRS differences in voluntary body sway most possibly indicate that low-frequency musical features rather than just tempo and pulse clarity are also important.